The Study of Oral cleanness Between Tooth brushing and Tooth pick plaque scaling. - เลาหกุล กมล (Thai Dental Public Health Journal, 2008)
Daily tooth brushing left large amount of plaque, increased chance to make oral disease. Toothpick was the first oral cleansing device, easy to find, cheap price. Everyone could use toothpick to clean oral cavity, to improve oral cleanness. The objectives of this study were to compare oral cleanness after tooth brushing and tooth picking in 20 primary school students. Everyone received scaling, polishing, 2 weeks brushing, 2 weeks tooth picking, chewing disclosing tablet and plaque examination. Tooth brushing and tooth picking had residual plaque at lower teeth more than upper teeth and the most at lingaul side of lower teeth. Tooth brushing showed continuous band of residual plaque less than 1 millimeter at cervical area of tooth surface. Tooth picking showed discrete residual plaque at cervical area and proximal tooth surfaces. Plaque residual after tooth brushing and tooth picking were difference statistically significance (MannWhitney test, P=0.01). Tooth brushing showed 3 clean teeth (0.71%) and tooth picking showed 83 clean teeth (19.76 %). Regular tooth brushing and tooth picking could be done in real-live, sustained for invidual level and community level, and increased chance for everyone to fully participate in oral health promotion and prevention.